Copy Fights: The Future of Intellectural Property in the Information Age - Thierer, Adam D; Crews, Clyde Wayne (Cato Institute, 2002)
The "Napsterization" of just about everything digitizable -- books, music, movies, and, of course, software itself -- has brought copy protection issues to the forefront as never before.